Trends in serum lipids among 5th grade CARDIAC participants, 2002–2012. Issue 3 (11th November 2013) - Lilly, Christa L; Gebremariam, Yohannes Daffo; Cottrell, Lesley; John, Collin; Neal, William
Abstract : Background: Studies have shown that serum low-density lipoprotein (LDL-C) and non-high-density lipoprotein (non-HDL-C) have recently declined in the USA among adult and child populations despite high obesity prevalence rates. The purpose of this study was to assess whether there was a significant linear decrease in LDL-C and non-HDL-C, but not Body Mass Index (BMI) percentile among a cross-sectional, large, homogenous cohort with consistent methodology over the past decade. Methods: A total of 47 198 children, mostly between 10 and 11 years old, participating between 2002 and 2012 were examined to assess trends in serum lipid concentration and BMI percentile. Results: For LDL-C, year of screening was significant (p<0.0001) even with the inclusion of gender, age and BMI (all p<0.0001). For non-HDL-C, year of screening was also significant (p<0.0001), even with the inclusion of gender (p=0.0445), age (p<0.0001), BMI (p<0.0001) and systolic blood pressure (p=0.0021). Although some non-linear trends were also significant (eg, a quartic trend, p<0.001), the linear trend provided the best fit for both cholesterol models. By comparison, we noted general maintenance of BMI percentile over time. Conclusions: Between 2002 and 2012, among 5th grade Appalachian children, there was a consistent linear decrease in LDL-C and non-HDL-C despite continued high prevalence rates of obesity, diabetes and hypertension. The improvement in LDL-C and non-HDL-C could be due to multifactorial causes.